Rodent Models of Non-classical Progesterone Action Regulating Ovulation - Mittelman-Smith, Melinda A.; Rudolph, Lauren M.; Mohr, Margaret A.; Micevych, Paul E. (Frontiers in Endocrinology, 2017)
It is becoming clear that steroid hormones act not only by binding to nuclear receptors that associate with specific response elements in the nucleus, but also by binding to receptors on the cell membrane. In this newly discovered manner, steroid hormones can initiate intracellular signaling cascades which elicit rapid effects such as release of internal calcium stores and activation of kinases. We have learned much about the translocation and signaling of steroid hormone receptors from investigations into estrogen receptor (ER), which can be trafficked to, and signal from, the cell membrane. It is now clear that progesterone (P4) can also elicit effects that cannot be exclusively explained by transcriptional changes. Similar to E2 and its receptors, P4 can initiate signaling at the cell membrane, both through progesterone receptor (PGR) and via a host of newly discovered membrane receptors (e.g., mPRs, PGRMCs). This review discusses the parallels between neurotransmitter-like E2 action and the more recently investigated non-classical P4 signaling, in the context of reproductive behaviors in the rodent.